2022
DOI: 10.3390/biomedicines10081851
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Bacteria for Improving Hypoxemia of COVID-19 Patients

Abstract: Background: Although useful in the time-race against COVID-19, CPAP cannot provide oxygen over the physiological limits imposed by severe pulmonary impairments. In previous studies, we reported that the administration of the SLAB51 probiotics reduced risk of developing respiratory failure in severe COVID-19 patients through the activation of oxygen sparing mechanisms providing additional oxygen to organs critical for survival. Methods: This “real life” study is a retrospective analysis of SARS-CoV-2 infected p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In conclusion, our data can partially explain the beneficial effects recorded following treatment with SLAB51 in animal models and patients with hypoxia-related conditions [31][32][33][34][35][36]. Despite this, to furnish the multi-strain SLAB51 probiotic with an authorized health claim approved by a regulatory agency, such as the U.S. Food and Drug Administration (FDA) or the European Food Safety Authority (EFSA), evidence has to be provided through well-designed human trials.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In conclusion, our data can partially explain the beneficial effects recorded following treatment with SLAB51 in animal models and patients with hypoxia-related conditions [31][32][33][34][35][36]. Despite this, to furnish the multi-strain SLAB51 probiotic with an authorized health claim approved by a regulatory agency, such as the U.S. Food and Drug Administration (FDA) or the European Food Safety Authority (EFSA), evidence has to be provided through well-designed human trials.…”
Section: Discussionmentioning
confidence: 93%
“…SLAB51 is a probiotic mixture consisting of Streptococcus thermophilus (DSM 32245), B. lactis (DSM 32246), B. lactis (DSM 32247), L. acidophilus (DSM 32241), L. helveticus (DSM 32242), L. paracasei (DSM 32243), L. plantarum (DSM 32244), and L. brevis (DSM 27961), previously studied both in vitro and in vivo, in animal models and patients, on hypoxia-related conditions [31][32][33][34][35][36]. Bacterial species present within this multi-strain probiotic formulation constitute common inhabitants of the human gut, mostly ingested with food, especially dairy products [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…We included 18 studies (11 RCTs and 7 observational studies) in our review (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). The details of the screening process are presented in Figure 1.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Probiotics can also release substances or induce direct responses from the host cells by influencing specific metabolic pathways and could also positively impact body sites other than the colon due to communication axes linking the colonic microbes with other organs and tissues [22][23][24]. Studies on adult COVID-19 patients with pneumonia have shown that administering multi-strain probiotics, i.e., SLAB51, could increase oxygenation [15,16]. Since the effect on oxygen saturation generally occurs as early as 2-3 h after ingestion, while any ingested food takes 6-8 h to reach and pass the ileocecal valve, it has been postulated that SLAB51 exerts its action in the intestine before colonizing the colon.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, the administration of the multi-strain probiotic SLAB51 was associated with significantly higher blood levels of both the partial pressure of oxygen (pO 2 ) and the arterial oxygen saturation (SaO 2 ) in adult COVID-19 patients with pneumonia treated with non-invasive ventilation [15,16]. These results highlight the ability of this multi-strain probiotic formulation to influence the redistribution of oxygen throughout the body through a possible oxygen-sparing effect involving the stabilization of HIF1α at the intestine level, in agreement with results published by Lombardi and colleagues [17].…”
Section: Introductionmentioning
confidence: 99%